(3efgL GdebGd aj JMbjb CMhGd GdQLGd (B((3QLGd GdTjYI(B)s - (3GdejQRG eMeO GdGSJQHGPj , eMeO Hf Ydj Hf EHQGgje GdaGQSj,J (B1028 (3g` s ((3GSeGYjd Hf SGde GdQGLi GdfLai s)
(3ChdgG (B:s
(3CeG HYO agPG cJGH MGhdJ ajg PcQ eG hUd Edi ef cdGe YdeGFfG GdJbOejf hGdeJCNQjf s
(3BNQgG (B:s
(3aQZ eDdag GdQGMi MGeOnG ddg eSJZaQkG eUdjkG Ydi GdfHi hBdg hGdCeLGO s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B293 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B298s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B385 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B305 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJGQjNs